Synergistic enhancement of antitumor effect of β-Lapachone by photodynamic induction of quinone oxidoreductase (NQO1) - Lamberti, María Julia (2013)
-Lapachone is a phytochemotherapeutic originally isolated from Lapacho tree whose extract has been used medicinally for centuries. It is well known that NAD(P)H:quinone oxidoreductase (NQO1) activity is the principal determinant of -Lapachone cytotoxicity. As NQO1 is overexpressed in most common carcinomas, recent investigations suggest its potential application against cancer. Photodynamic therapy (PDT) is a clinically approved and rapidly developing cancer treatment. PDT involves the administration of photosensitizer (PS) followed by local illumination with visible light of specific wavelength. In the presence of oxygen molecules, the light illumination of PS can lead to a series of photochemical reactions and consequently the generation of cytotoxic reactive oxygen species (ROS). It has been reported that -Lapachone synergistically interacts with ionizing radiation, hyperthermia and cisplatin and that the sensitivity of cells to -Lapachone is closely related to the activity of NQO1. So,the present study aimed to investigate the feasibility of PDT to increase the anticancer effect of -Lapachone by up-regulating NQO1 expression on breast cancer MCF-7c3 cells. NQO1 expression was evaluated by Western blot analysis at different times after PDT using ME-ALA as PS. The cytotoxicity of the photodynamic treatment and -Lapachone alone or in combination was determined by MTT assay and the combination index (CI)- isobologram method and the dose reduction index (DRI) analysis were used to assess the effect of drug combinations. Our studies for the first time demonstrated that the expression of NQO1 is induced 24 h after photodynamic treatment. The sensitivity of cancer cells to -Lapachone treatment increased 24 h after PDT and a synergistic inhibitory effect on MCF-7c3 cells was showed. Taken together, these results lead us to conclude that the synergistic interaction between -Lapachone and PDT in killing cells was consistent with the up-regulation of NQO1. The combination of -Lapachone and PDT is a potentially promising modality for the treatment of cancer.